Person-centred counselling in action - Mearns, Dave.; Thorne, Brian, 1937-; McLeod, John, 1951- (London ; Thousand Oaks, Calif. : SAGE, 2013)
This important Fourth Edition maintains the book's accessibility, clarity and verve whilst incorporating new developments in the approach. John McLeod joins authors Dave Mearns and Brian Thorne to contribute an exciting new chapter on research relevant to the person-centred field.
Basic theory of the person-centred approach -- Recent developments in person-centred theory -- The counsellor's use of the self -- Empathy -- Unconditional positive regard -- Congruence --'Beginnings' --'Middles' --'Endings' -- Reseach on person-centred counselling.
Previous ed.: published as by Dave Mearns and Brian Thorne. 2007.
Includes bibliographical references (p. [208]-223) and indexes.
Keywords: Counseling